City of God and Pancasila: How divine value influences legal products in Indonesia - Alfido Fiqri Arsy Adhiem; Katherine Amalia Lussiana Olislager; Tamara Setiana; Sahara Meriola Putri (Priviet Social Sciences Journal, 2026)
Oneness of God is one of the basic philosophies in Pancasila that serves as the basic norm for the formation of all legal products in Indonesia. Interestingly, the philosophy of Oneness of God is similar to St. Augustine's Civitas Dei (City of God) doctrine, in which he argues that a state has to base its philosophy on eternal universal values in God. This article aims to examine some relevances and differences between St. Augustine's philosophical doctrine of Civitas Dei and the Oneness of God in Pancasila as a state philosophy, which ultimately influences the formation of legal products in Indonesia in accordance with Hans Kelsen’s Stufenbau theory. The research employs a normative legal research method with a conceptual and philosophical approach to form a qualitative descriptive analysis using primary and secondary legal materials as references. The results of this article show that the main relevance between the Oneness of God in Pancasila and St. Augustine's Civitas Dei is that only in God can all ideal and universal values ​​​​be found, and thus should be the state’s highest norm. Consequently, the Oneness of God in Pancasila becomes a primary influence in forming domestic legal products by referring to the Pancasila as the highest norm to which all legal products must refer. Following this philosophy, the formation of law in Indonesia based on divine value is a strong reference to avoid the formation of law based on the personal ambitions of the rulers.